Muḥammad ‘Amīm Al Iḥsān’s Approach in the Science of Riwāyah and Dirāyah - Hosain, Muhammad; Ramchahi, Abdollatif Ahmadi; Ahmad Shah, Faisal (Online Journal of Research in Islamic Studies, 2018)
This study aims at studying the knowledge of Muḥammad ‘Amīm Al Ihsān in Ḥadīth Studies Riwāyah and Dirāyah through his book Fiqh al-Sunan wa Al-Athār. To the best of the researchers’ knowledge, no academic study has examined Iḥsān’s ability in Ḥadīth science, mainly in what concerns in the book of Ḥanafī schools of thoughts. This espouses the analytical inductive method to analyze the data. It begins by providing a brief introduction to Iḥsān and his celebrated book of Ḥadīth Fiqh al-Sunan wa al-Athīr. This followed by a discussion of his talent in Hadīth Riwāyah and Dirāyah. This discussion is divided into four examples modelled from his many examples of Riwāyah and Dirāyah in this book, namely his methodological rirāyah in al-Jarh wa al-Taʻdīl, his riwāyah in repeating ḥadīth, his methodological dirāyah in solving the apparent contradiction between two Hadīth and his methodological dirāyah in explaining ḥadīth.